Development of An Artificial Conversational Entity As A Virtual Agent Top Offer Automated Helpdesk Support In College Housing Deveopment - Difo, Aldiaz (2010)
The Idea of implementing a form of artificial intelligence entity to offer an automated helpdesk support is, like a great many other ideas and disciplines. This particular idea (henceforth referred to as simply ‘automated helpdesk’) was not merely inspired by these older areas, in which case one may divorce the links between them and proceed to treat it as a fundamentally independent implementation: these entities are still instances of those areas and must adhere to whatever principles, definitions and heuristics applicable to any other instance. It should follow from there that, prior to investigating the current state of affairs regarding automated helpdesks, one is advised to cover the topics of those aforementioned ideas and disciplines from which automated helpdesks sprung.